Utilization of Youtube Channels in Kua Ujung, Parepare City in Forming Sakinah Family - Abidin, Zainal (IAIN Parepare, 2021)
This thesis is about the Use of a YouTube Channel at the KUA Ujung Kota Parepare in Forming a Sakinah Family. This research uses descriptive qualitative research. The results of this study indicate: (1) Utilization of the Youtube channel: KUA Ujung Parepare, containing content related to guidance and marriage (bimwin) materials such as the meaning of the sakinah family, the rights and obligations of husband and wife, thaharah material (mandi junub), family economic management, practice of consent qabul, ways of educating children, maintaining reproduction and material on Domestic Violence (KDRT). (2) Supporting factors in using the youtube channel at KUA Ujung Parepare are: the community's need for information about the sakinah family, easy access to youtube services. Meanwhile, the inhibiting factors in using YouTube channels are: lack of content publication, limited knowledge of access to YouTube channels, and it takes a long time to access YouTube channels. (3) Utilization of the youtube channel: KUA Ujung Parepare in forming a sakinah family in Ujung Parepare City which has a significant role and contribution in getting to the sakinah family, especially in increasing the knowledge and understanding of the bride and groom in forming sakinah , mawaddah and warahmah families.